Comparison of Intraocular Lens (IOL) Implantation with and without Capsular Tension Ring (CTR) Placement in Cataractous Dogs - Santosh, H. K.; Ranganath, L.; Nagaraja, B. N.; Satyanarayana, M. L.; M. Narayanaswamy (International Journal of Livestock Research, 2019)
The objective of the present study was to compare the implantation of intraocular lens (IOL) with and without Capsular Tension Ring (CTR) placement and its efficacy in decreasing the occurrence of posterior capsule opacification (PCO) after phacoemulsification in cataractous dogs. Twelve client-owned dogs with mature cataracts were divided into IOL alone and CTR/IOL groups comprising six dogs in each group. The eyes were randomly selected to receive IOL alone or in association with the CTR. Clinical evaluations were conducted on day 0, 1st, 3rd, 7th, 14th, 21st, 30th, 60th, 90th, 120th, 150th, 180th and 210th day. IOL group recorded 50% PCO as compared to CTR/IOL group, where it was recorded as 16.67% at the end of the study period. These results suggest CTR could be useful in the prevention of the post-operative capsule opacities, with minor complications.